Interaction between atypical microorganisms and E. coli in catheter-associated urinary tract biofilms - Azevedo, Andreia (2014)
Most biofilms involved in catheter-associated urinary tract infections (CAUTIs) are polymicrobial, with disease causing (eg Escherichia coli) and atypical microorganisms (eg Delftia tsuruhatensis) frequently inhabiting the same catheter. Nevertheless, there is a lack of knowledge about the role of atypical microorganisms. Here, single and dual-species biofilms consisting of E. coli and atypical bacteria (D. tsuruhatensis and Achromobacter xylosoxidans), were evaluated. All species were good biofilm producers (Log 5.84–7.25 CFU cm−2 at 192 h) in artificial urine. The ability of atypical species to form a biofilm appeared to be hampered by the presence of E. coli. Additionally, when E. coli was added to a pre-formed biofilm of the atypical species, it seemed to take advantage of the first colonizers to accelerate adhesion, even when added at lower concentrations. The results suggest a greater ability of E. coli to form biofilms in conditions mimicking the CAUTIs, whatever the pre-existing microbiota and the inoculum concentration.